Welfare Impact of Organic Fertilizer Adoption: Empirical Evidence From Nigeria - Oyetunde-Usman, Zainab; Ogunpaimo, Oyinlola Rafiat; Olagunju, Kehinde Oluseyi; Ambali, Omotuyole Isiaka; Ashagidigbi, Waheed Mobolaji (Frontiers in Sustainable Food Systems, 2021)
Soil fertility depletion is acknowledged to adversely influence agricultural productivity and welfare status of rural farming households. Studies have shown that organic fertilizer utilization tends to rejuvenate the soil, thereby enhancing its productive capacity. This study seeks to estimate the welfare impact of organic fertilizer adoption among agricultural households using the 2018/2019 Nigeria General Household Survey (GHS). The novelty of this study is in the use of propensity score matching (PSM) and endogenous treatment regression (ETR) to address biases that may arise from both observed and unobserved factors. Results show that the adoption of organic fertilizers positively and significantly impacts the welfare of farmers, particularly when sources of unobserved characteristics of agricultural households are accounted for. The heterogeneity impact results show that female household heads, agricultural households that had access to credit, and farm household residents in the southern region of Nigeria significantly gained more from the adoption of organic fertilizers. In addition, a check for time effect reveals that the adoption of organic fertilizers does not result in an immediate welfare effect; the effect is, however, positive and significant over time. This suggests that adoption does not only improve soil and mitigate against climate impact, but it also has a higher likelihood of providing long-term and sustainable welfare impact for agricultural households. The results point to the need for policies and programs to promote and sustain the adoption of organic fertilizers among agricultural households through addressing existing institutional barriers such as extension and credit facilities.